Miss Heather Tate, Rod Dixon, and Dan Powers - Unknown:::Creator::::::::::::
Photograph shows Miss Heather Tate, Rod Dixon and Dan Powers. They are passing a cup and plate and standing in front of a fireplace with a painting above it.